COMPARATION BETWEEN METHADONE AND BUPRENIRFINE THERAPY - Spasovska Trajanovska, Aneta (SHMSHM/AAMD, 2022)
Heroin dependence is a major health and social problem associated with increased morbidity and mortality that adversely affects social circumstances, productivity, healthcare and law enforcement cost. Methadone and buprenorphine are the major modalities of the opioid substitution therapy. (OST) for opioid dependence in North Macedonia. Also some researchers reported that illicit heroin use is an international problem. Opiate use or dependence is destructive in many levels, it is associated with higher rates of hepatitis C and HIV infection, overdose and criminality. Buprenorphine and methadone each have specific advantages and disadvantages. Properly and judiciously used, either can help suitably selected patients avoid illicit opioid use while improving mental health and quality of life. The AIM pf this study is to compare the efficiency between methadone and buprenorphine therapy. MATERIJALS AND METHODS.The cross section present study included two groups of male patients: on methadone (n=50) and patients on buprenorphine therapy (n=50) , between 20-51 years, evaluated in Day hospital of heroin addicts- department of Psychiatric Hospital Skopje with diagnosis of opiate addictions F11.2 The study was conducted for 6 month. All the patients was written informed consent. The patients were assess using the sociodemographic information by semi-structured questionnaire specially designed for the study. The sociodemographic data was: age, marital status, education status and employment. Urinary tests for determination of psychoactive substances. Blood test for hepatitis C detection. The sexual function in man was assess by Questionnaire International Index of Erectile Function (IIEF-scale). The results of this study were determinate by descriptive methods, t-test for independent simplex .and Pearson coefficient correlation. P<0.05 was considered statistically significant. RESULTS: In our study we got that the level of education (p=0, 05); marital status (p=0, 07); employment (p=0, 08) was higher in patients with buprenorphine therapy but without statistical significantly. Also the recidivism of heroin use (p=0, 02), benzodiazepine (p=0, 03) and cocaine use (p=0, 05) was statistically significant higher in patients with buprenorphine therapy, but retention on treatment was higher in methadone maintenance patients without statistically significant. When compare correlation between score of sexual dysfunction and dose of methadone and buprenorphine therapy we got positive correlation , but is was higher and with statistically significant in patients with methadone therapy than patients with buprenorphine therapy Also we got higher percentage of sexual dysfunction in methadone maintenance patients 65,3/34,7% than buprenorphine therapy.35.8/64,2 The results in this study reported no differences between patients with hepatitis C on substitution treatment p=0, 72 CONCLUSION: Results in our studies, suggested that buprenorphine therapy improves the quality of patients’ social development while methadone therapy diminished heroin recidivism. This knowledge creates an opportunity for doctors to convert OST therapy depending on the need.
Keywords: methadone therapy; buprenorphine therapy; heroin addict’s patients